Cancer registry data based estimation of regional cancer incidence: application to breast and colorectal cancer in French administrative regions. Issue 9 (1st September 1999) - Colonna, M; Grosclaude, P; Faivre, J; Revzani, A; Arveux, P; Chaplain, G; Tretarre, B; Launoy, G; Lesec'h, J M; Raverdy, N; Schaffer, P; Buémi, A; et al.
Abstract : STUDY OBJECTIVE: In many countries, cancer registries cover only a small part of the national population. Cancer incidence for the rest of the country has therefore to be estimated. This can be done from mortality data using the relation between incidence and mortality observed in the cancer registry areas. Such an approach was used to study geographical variation and trend of colorectal and breast cancer incidence in France where 10% of the national population is covered by cancer registries. DESIGN: This study applies the incidence/mortality ratios of cancer registry areas to regional mortality data to obtain an estimation of cancer incidence at a given point in time. Age and period effects are included in the statistical models. MAIN RESULTS: The incidence estimations are given for 21 administrative regions and three time points (1985, 1990, 1995). The European standardised incidence rates for breast cancer ranged from 86.8 to 128.8. For colorectal cancer, these rates ranged from 48.2 to 79.6 for men, and from 32.5 to 48.8 for women. Breast cancer incidence has increased considerably between 1985 and 1995 with a higher increase in the north than in the south of France. The incidence of colorectal cancer has also increased, albeit to a lesser extent. CONCLUSION: The incidence estimation method proposed leads to regional incidence rates that are useful for planning health care services on a regional basis and may also be used to study regional differences in incidence. This method is useful when only partial incidence data are available.